Innovations in rural and agricultural finance: M-PESA: Finding new ways to serve the unbanked in Kenya - Lonie, Susie (International Food Policy Research Institute, 2010)
Over the past three years, payment strategies for emerging markets have been revolutionized by the advent of a simple cell-phone-based payment service in Kenya called M-PESA (“M” for “mobile” and “pesa” for “money”). From a small-scale pilot program in 2006, M-PESA has become an outstanding success in Kenya; customer response has been unprecedented. Currently, more than 9 million Kenyans use M-PESA to perform tens of millions of transactions every month throughout the country. Although this success has led to new opportunities, it has also brought about many unforeseen challenges.